Does continuous infusion of local anaesthesia improve pain control and walking distance after coronary artery bypass graft surgery? A randomised controlled trial. Issue 4 (December 2017) - Hong, Serena S.; Alison, Jennifer A.; Milross, Maree A.; Robledo, Kristy; Dignan, Rebecca
Abstract: Objectives: To evaluate the effects of continuous infusion of ropivacaine compared to sham infusion or usual care on pain scores before and after physiotherapy treatment, distance walked and time to discharge from physiotherapy, after coronary artery bypass graft (CABG) surgery. Design: Prospective, randomised, double blind controlled trial. Setting and participants: Seventy-five participants who underwent CABG surgery with left internal mammary artery grafts were allocated, to the ropivacaine group (n = 26), the sham group (n = 25), or usual care group (n = 24). Participants in the ropivacaine group received 0.5% ropivacaine and participants in the sham group received normal saline, both as continuous infusions via two parasternally tunnelled catheters for 96 hours continuously. The usual care group did not receive a device. All groups had patient-controlled analgesia and/or oral analgesia. Results: Seventy-two participants completed the study. There was no significant between-group differences in pain scores, distance walked on any post operative day (POD) or number of participants discharged from physiotherapy by POD 4. For the group as a whole there was a significant linear decrease in pain score from mean (SD) 42 (24) mm on POD1 to 15 (16) mm on POD4 (p < 0.001), (MD 27 mm, 95% CI 22 to 32) and walking distance increased from 1 (5) m on POD1 to 183 (239) m on POD4 (p < 0.001) MD 181 m, 95% CI 126 to 236). Conclusion: Infusion of ropivacaine post CABG surgery was unable to reduce pain, increase distance walked or reduce time to physiotherapy discharge compared to sham or usual care. Trial registration number ACTRN12612001243808.